Physical ageing and thermal analysis of PLGA microspheres encapsulating protein or DNA - Rouse, J. J.; Mohamed, Farahidah; van der Walle, Christopher (Elsevier Inc., 2007)
PLGA microspheres undergo physical ageing but their ageing kinetics have not been reported, nor the effect of encapsulated protein or plasmid DNA on any associated changes to the glass transition. Differential scanning calorimetry (DSC) was used to measure the rate of ageing of various PLGAmicrosphere formulations, with temperature-modulatedDSCused to accurately measure the associated glass transition. The Cowie–Ferguson model was applied to determine the parameters describing the enthalpy relaxation kinetics. We show that encapsulated proteins had no significant effect on the glass transition of the microspheres, whereas DNA and PVA were mild antiplasticising agents, particularly with high Mw PLGA. Physical ageing occurred through a range of enthalpy relaxation times (or modes) and was independent of both encapsulated protein and surfactant used during microsphere preparation. Analysis of accelerated ageing at 35 ◦C gave calculated enthalpy relaxation times to thermal equilibrium of 280–400 h. No ageing was observed ≤10 ◦C and at 25 ◦C estimated relaxation times were at least one order of magnitude greater than at 35 ◦C. Ageing of PLGA microspheres therefore occurs at temperatures >10 ◦C, but relaxation will be far from equilibrium unless storage times and/or temperatures are prolonged or nearing the glass transition, respectively.